EFEKTIVITAS PENERAPAN BELOK KIRI LANGSUNG (Studi Kasus Jalan Soeprapto Kota Bengkulu) - Samsul Bahri; Vitria Elsandiy (Inersia: Jurnal Teknik Sipil, 2019)
RI Act No. 22 of 2009 states that on the intersection traffic light drivers are prohibited from turning left immediately, unless specified otherwise by traffic signs. This study aims to determine the effectiveness of the ‘left turn on red’ signal and its effect on the capacity of Simpang Lima Bengkulu city.The results showed that in terms of the degree of saturation, the capacity of Simpang Lima Bengkulu city at Soeprapto roads site is better whenever it is applied the left turn on red signal. It is necessary to evaluate the traffic light settings on Simpang Lima Bengkulu City because the degree of saturation has exceeded the tolerance limits suggested byMKJI 1997.